Liquid-Phase Polymer-Based Retention to Remove Arsenic from Water - Sanchez-Poblete, J (Sociedad Chilena de Quimica, 2019)
The functional polymer materials have presented a great development in adsorption processes for the treatment of polluted waters. The aim of the current review is to present the developments during the few last years in this field of study by examining research of systems like water-functional soluble polymers and electro-oxidation process coupled to ultrafiltration membranes for decontamination processes in liquid-liquid phase. The study is addressed to arsenic which is considered one of the most hazardous contaminants. © 2019 Sociedad Chilena de Quimica. All rights reserved.